Differences of Macroalgal Consumption by Eight Herbivorous Coral Reef Fishes From the Xisha Islands, China - Wu, Peng; Wang, Teng; Liu, Yong; Li, Chunhou; Xiao, Yayuan; Xu, Shannan; Han, Tingting; Lin, Lin; Quan, Qiumei (Frontiers in Marine Science, 2022)
Herbivorous fishes play an important role in preventing the overabundance of macroalgae on coral reefs. Understanding the feeding selectivity and consumption of macroalgae by herbivorous fishes can be challenging in studies of their ecological role in the preservation and recovery of coral reefs. Coral reef decline, macroalgal overgrowth and overfishing are clearly visible in the Xisha Islands, China. However, there have been no studies of the feeding behaviors of herbivorous fishes in this area. We used microscopy, 18S rRNA high-throughput sequencing, and stable isotope analyses to comprehensively examine the dietary spectrum of eight herbivorous reef fish species common in the Xisha Islands, including one parrotfish, two chub, two unicorn fish, and three rabbitfish. Multi-technique analyses of intestinal contents revealed that Kyphosus vaigiensis, Naso unicornis and Siganus argenteus showed a high consumption potential of macroalgae, suggesting that they are the key browsers that should receive priority protection in the Xisha Islands. Kyphosus cinerascens, K. vaigiensis, N. unicornis and S. punctatissimus fed on the entire macroalgal thallus, indicating their greater ecological importance compared with species that only consume algal fronds. However, Calotomus carolinus can consume the red alga Pneophyllum conicum, which is widely distributed on Indo-Pacific coral reefs and can overgrow and kill live corals. A diverse herbivorous fish fauna is very important in the Xisha coral reefs. These results not only demonstrated the various functions of different herbivorous fish species in macroalgal removal, but also provided insights into the management of herbivorous fishes on the coral reefs of the South China Sea.